2022
DOI: 10.1038/s43247-022-00504-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid 20th century warming reverses 900-year cooling in the Gulf of Maine

Abstract: The Gulf of Maine, located in the western North Atlantic, has undergone recent, rapid ocean warming but the lack of long-term, instrumental records hampers the ability to put these significant hydrographic changes into context. Here we present multiple 300-year long geochemical records (oxygen, nitrogen, and previously published radiocarbon isotopes) measured in absolutely-dated Arctica islandica shells from the western Gulf of Maine. These records, in combination with climate model simulations, suggest that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…Sedimentary records of an increase in TCs during this interval have also been found elsewhere at several sites through the WNAB (e.g., Thatchport, Bahamas, van Hengstum et al., 2013; Mattapoisett Marsh, MA, Boldt et al., 2010; Lighthouse Bluehole, Belize, Denommee et al., 2014). Multiproxy analysis (oxygen, nitrogen, and radiocarbon isotopes) carried out in the Gulf of Maine indicates that there was a significant SST warming there that commenced in the late nineteenth century (2.2°C per century), as the LIA came to an end (Whitney et al., 2022). This increase in temperature has been linked to a renewed weakening of the AMOC, as hypothesized to have occurred during LIAa, that would have forced the Gulf Stream to a position closer to the Gulf of Maine (Thibodeau et al., 2018; Zhang & Vallis, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sedimentary records of an increase in TCs during this interval have also been found elsewhere at several sites through the WNAB (e.g., Thatchport, Bahamas, van Hengstum et al., 2013; Mattapoisett Marsh, MA, Boldt et al., 2010; Lighthouse Bluehole, Belize, Denommee et al., 2014). Multiproxy analysis (oxygen, nitrogen, and radiocarbon isotopes) carried out in the Gulf of Maine indicates that there was a significant SST warming there that commenced in the late nineteenth century (2.2°C per century), as the LIA came to an end (Whitney et al., 2022). This increase in temperature has been linked to a renewed weakening of the AMOC, as hypothesized to have occurred during LIAa, that would have forced the Gulf Stream to a position closer to the Gulf of Maine (Thibodeau et al., 2018; Zhang & Vallis, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This increase in temperature has been linked to a renewed weakening of the AMOC, as hypothesized to have occurred during LIAa, that would have forced the Gulf Stream to a position closer to the Gulf of Maine (Thibodeau et al., 2018; Zhang & Vallis, 2007). Warmer water conditions in the Gulf of Maine, with possibly the highest SSTs recorded there during the past 1,000 years (Whitney et al., 2022), would have provided a conduit for storms to track into southern NB. In contrast, other researchers have concluded that the AMOC was not significantly altered during the LIA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the northwestern Atlantic, we have not seen similar poleward movement in D. cuprea [ 35 ]—at least, not as of 2022 (Berke unpublished data). This is somewhat surprising, as the Gulf of Maine has been warming rapidly [ 88 ]. Whether this reflects different thermal biology, constraints of larval supply, lack of intertidal aquacultural transport, or something else remains an open question.…”
Section: Human Impactsmentioning
confidence: 99%
“…Over the last decades, the Slope Sea and northeastern American continental shelf have experienced an increase in water temperatures and a decrease in oxygen concentrations (Chen et al, 2020;Claret et al, 2018;Petrie and Drinkwater , 1993, among others), including in connected bodies of water such as the St. Lawrence Estuary (Jutras et al, 2020;Gilbert et al, 2005) and the Gulf of Maine (Whitney et al, 2022;Pershing et al, 2016), with dire consequences on marine ecosystems (Poitevin et al, 2019;Chabot and Dutil , 1999) and fisheries (Pershing et al, 2016;Mills et al, 2013). From 2012 to 2016, the subpolar North Atlantic experienced a strong freshening (Holliday et al, 2020), with potential impacts on the Atlantic meridional overturning circulation (AMOC, Holliday et al, 2020;New et al, 2021).…”
Section: Introductionmentioning
confidence: 99%